Performance of Pre- and Post-emergence herbicides in strip tillage Non-puddled transplanted Aman rice - Zahan, T; Rahman, MM; Hashem, A; Bell, RW; Begum, M (Bangladesh Journal of Agricultural Research, 2018)
A study was conducted on transplanted aman rice (cv. BINA dhan-7) in strip-tilled non-puddled field with some commonly used rice herbicides (pre-emergence: pyrazosulfuron-ethyl and butachlor, early post-emergence: orthosulfamuron and late post-emergence: acetochlor + bensulfuron methyl, butachlor + propanil and 2,4-D amine) applied singly or in sequences during 2013 and 2014 at field laboratory, Bangladesh Agricultural University, Mymensingh to evaluate the effect of those herbicides on weeds as well as growth and yield of aman rice in strip-tilled non-puddled condition. The study showed that herbicides significantly reduced weed density by 75-94% in 2013 and 46-98% in 2014 compared to the weedy check. Sole application of pre- or early post-emergence herbicide provided less weed control than sequential application of pre-, early post- and late post-emergence herbicides or application of pre- and late post-emergence herbicides. A wide range of sequential application of herbicide treatments has identified in the study that provided control on weed density and biomass by 49-98% and 56-95%, respectively. Application of pyrazosulfuron-ethyl followed by orthosulfamuron and butachlor + propanil was the most effective combination in this new rice establishment condition that controlled all types of weeds successfully and provided maximum grain yield (5.42 t ha-1 in 2013 and 6.18 t ha-1 in 2014) with highest economic return (Tk. 55930 ha-1 in 2013 and Tk. 69057 ha-1 in 2014). The study suggests economically beneficial some combinations of currently used herbicides for strip-tlled non-puddled transplanted aman rice that may help farmers to choose and rotate in the same land yearwise for obtaining optimum yield. Bangladesh J. Agril. Res. 42(4): 631-646, December 2017